👤

demonstrați :
[tex] \frac{1 + \cos(4x) }{ \sin(3x) - \sin(x) } = \frac{ \cos(x) }{ \sin(x) } [/tex]



Răspuns :

Răspuns:

[tex]\frac{1+cos(4x)}{sin(3x)-sin(x)}=\frac{cos(2x)}{sin(x)}[/tex]

Fac separat 1+cos(4x) si sin(3x)-sin(x)

[tex]1+cos(4x)=cos(0)+cos(4x)=2cos\frac{0+4x}{2}*cos\frac{0-4x}{2}=2cos(2x)*cos(-2x)[/tex]

[tex]=2cos(2x)*cos(2x)=2cos^2(2x)[/tex]

[tex]sin(3x)-sin(x)=2sin\frac{3x-x}{2}*cos\frac{3x+x}{2}=2sin(x)*cos(2x)[/tex]

Inlocuim:

[tex]\frac{2cos^2(2x)}{2sin(x)*cos(2x)}=\frac{cos(2x)}{sin(x)}[/tex] "Adevarat"